2019
DOI: 10.1177/2150132719861265
|View full text |Cite
|
Sign up to set email alerts
|

Depression Outcomes in Smokers and Nonsmokers: Comparison of Collaborative Care Management Versus Usual Care

Abstract: Background: Depression is common in the primary care setting and tobacco use is more prevalent among individuals with depression. Recent research has linked smoking to poorer outcomes of depression treatment. We hypothesized that in adult primary care patients with the diagnosis of depression, current smoking would have a negative impact on clinical outcomes, regardless of treatment type (usual primary care [UC] vs collaborative care management [CCM]). Methods: A retrospective chart review study of 5155 adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For the relationship between smoking and depression, our results, using improved genetic instruments compared to prior studies, are consistent with previous evidence supporting a reciprocal association between these variables. Observational evidence has shown that depression can trigger smoking commencement and make its cessation more challenging [59][60][61][62][63] . Moreover, smoking has been shown to lead to depression, and smoking cessation has been associated with improved depressive outcomes and decreased depression symptomatology [63][64][65] .…”
Section: Smoking and Depressionmentioning
confidence: 99%
“…For the relationship between smoking and depression, our results, using improved genetic instruments compared to prior studies, are consistent with previous evidence supporting a reciprocal association between these variables. Observational evidence has shown that depression can trigger smoking commencement and make its cessation more challenging [59][60][61][62][63] . Moreover, smoking has been shown to lead to depression, and smoking cessation has been associated with improved depressive outcomes and decreased depression symptomatology [63][64][65] .…”
Section: Smoking and Depressionmentioning
confidence: 99%
“…On the contrary, smoking also affects the outcome of depression 25 . Mendelian randomization study 26 found that there is a two-way causal relationship between depression and smoking, and the two interact, forming a vicious circle.…”
Section: Discussionmentioning
confidence: 99%
“…For the relationship between smoking and depression, our results, using improved genetic instruments compared to prior studies, are consistent with previous evidence supporting a reciprocal association between these variables. Observational evidence has shown that depression can trigger smoking commencement and make its cessation more challenging 5054 . Moreover, smoking has been shown to lead to depression, and smoking cessation has been associated with improved depressive outcomes and decreased depression symptomatology 5456 .…”
Section: Discussionmentioning
confidence: 99%